Comparative analysis of various combustion phase control methods in a lean-burn H2/methanol fuel dual-injection engine. (15th February 2020) - Gong, Changming; Li, Zhaohui; Yi, Lin; Sun, Jingzhen; Liu, Fenghua
Highlights: Phasing of an ideal θ pmax and CA50 was used to determine optimal spark timing. Spark timing under different H2 addition ratios and equivalence rates was optimized. The higher H2 addition is, the later spark timing will be at same equivalence ratio. Using spark timing by θ pmax could achieve the best compromise of performance. Abstract: The combustion phase of the maximum in-cylinder pressure ( θ pmax ) and 50% heat release rate position (CA50) are often used to evaluate the reasonableness of the engine combustion. Spark timing is a decisive parameter that influences θ pmax and CA50 of spark-ignition engine. A H2 port-injection and methanol direct-injection dual-fuel engine was adopted to study the adjustment spark timing under low engine speed, lean-burn and methanol late-injection strategy by application constant θ pmax and CA50 combustion center. The performances of the adjustment spark timing by constant θ pmax and CA50 combustion center was compared with performances of maximum brake torque (MBT) spark timing under equivalence ratio 1.0. The results show that using constant θ pmax 16 °CA ATDC combustion center, the optimal spark timing was advanced as decreasing equivalence ratio. Using constant CA50 of 10 °CA ATDC combustion center, the optimal spark timing was also advanced as decreasing equivalence ratio. The higher the H2 addition ratio is, the later the optimal spark timing will be at same equivalence ratio. The optimal spark advance for addition H2 is smaller than that of pure methanol, and the optimal spark advance for 6% addition H2 is smaller than that of 3% addition H2 . The adjustment spark timing by θ pmax 16 °CA ATDC has good regularity. The adjustment spark timing by CA50 10 °CA ATDC is almost random. Using adjustment spark timing by θ pmax could achieve the best compromise of engine performance for with/without H2 addition methanol engines.